2003
DOI: 10.1542/peds.112.6.1345
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Pediatric Cardiac Surgery in Finland: Education, Employment, Marital Status, and Parenthood

Abstract: Our results confirm that in addition to high survival rate, the long-term psychosocial outcome of patients with surgically treated congenital heart defects is good if they do not have any additional syndromes that cause mental retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
36
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
11
36
7
1
Order By: Relevance
“…This is in accordance with a Finnish study (Nieminen et al 2003), but in two other reports the results had been into the opposite direction (Crossland et al 2005;Kamphuis et al 2002). Differences between studies examining employment status may also result out of country-specific prospects of providing jobs to women and men with impairments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in accordance with a Finnish study (Nieminen et al 2003), but in two other reports the results had been into the opposite direction (Crossland et al 2005;Kamphuis et al 2002). Differences between studies examining employment status may also result out of country-specific prospects of providing jobs to women and men with impairments.…”
Section: Discussionsupporting
confidence: 89%
“…In two of these studies employment of women and men had not been considered separately (Crossland et al 2005;Kamphuis, Vogels et al 2002), although they are differing with respect to part-time and full-time employment. In one study gender was controlled for (Van Rijen et al 2003), but in only one separate analyses for women and men had been performed (Nieminen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most patients with CHD appear to enjoy a good quality of life as adults [27][28][29][30][31][32] . In a detailed quality of life study from Belgium, 514 adults with CHD were compared to a matched control group from the general population at a median age of 23 years [33] .…”
Section: Adults With Chd-a Growing Population At Risk For Depression?mentioning
confidence: 99%
“…These trends have led to an increasing interest in the investigation of long-term psychological functioning, social aspects, perceived health status and quality of life of adult CHD survivors [3]. A number of studies have focused on employment and education, with most suggesting a negative impact imposed by CHD, albeit to varying degrees [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Nieminen et al compared data about psychosocial factors, including employment and educational level, in 2896 operated ACHD patients who answered a mailed questionnaire, with general Finnish population data and found no significant differences in educational and employment level [10]. All the other studies reported varying degrees of disadvantages for employment and/or educational achievements for ACHD patients, especially those with more complex disease.…”
mentioning
confidence: 99%